Pemodelan Dinamis Proses Produksi Batch Satu Tahap Dalam Satu Mesin Dengan Memperhatikan Waktu Loading dan Waktu Proses - Petrus Setya Murdapa; Chatarina Dian Indrawati; Theresia Liris Windyaningrum (Politeknik ATI Padang, 2024)
In the batch process, the company uses the same process facilities to produce various types of products. This allows businesses to change production in response to changes in market demand. Batch processes are widely used in industry. In many cases, batch processes provide several benefits over continuous processes, especially when the industry wants to ensure and maintain the quality standards of its products. This paper proposes a behavioral model of a single-stage batch processing system, using the language of system dynamics. When run, the behavioral model will provide an overview of how the system behaves. The system dynamics language is a formulation of a system of ordinary differential equations that is extracted from the real system being studied, in the form of a stock and flow diagram. The computation of this diagram is further implemented using software. Because it is actually a calculus method, the system dynamics language provides output data much faster than discrete simulation modeling. In this paper, the system behavior modeled is mainly loading, processing and unloading activities. The verification results carried out by testing it on two different case examples show that the model can sufficiently describe the behavior of the conceptual system logically so that the model can enrich experimental tool options related to batch production processes in the future.